1901. Safety, Tolerability, and Efficacy of Fluoxetine as an Antiviral for Enterovirus D68 Associated Acute Flaccid Myelitis: A Retrospective Multicenter Cohort Study. (26th November 2018) - Messacar, Kevin; Sillau, Stefan; Hopkins, Sarah; Otten, Catherine; Wilson-Murphy, Molly; Wong, Brian; Santoro, Jonathan; Treister, Andrew; Tokhie, Harlori; Torres, Alcy; Zabrocki, Luke; Glanternik, Julia; et al.
Abstract: Background: Most patients with enterovirus (EV) D68-associated acute flaccid myelitis (AFM) have long-term disability. No effective therapies have been identified. Fluoxetine is the only FDA-approved medication with in vitro antiviral activity against EV-D68. This study retrospectively analyzed the safety, tolerability, and efficacy of fluoxetine for EV-D68-associated AFM. Methods: A multicenter cohort study of US children with AFM in 2015–2016 compared serious adverse events (SAEs), adverse effects, and outcomes between fluoxetine-treated patients and untreated controls with AFM. Fluoxetine was administered at the discretion of treating providers with data gathered retrospectively. The primary outcome was summative limb strength score (SLSS; sum of Medical Research Council strength in all four limbs). Results: 56 patients with AFM from 12 centers met study criteria (Figure 1). Among 30 patients exposed to fluoxetine, no SAEs were reported and adverse effects were similar to controls ( P = 0.16). The 28 patients treated with >1 dose of fluoxetine were more likely to have EV-D68 identified (57.1% vs. 14.3%, P = 0.001). Fluoxetine-treated patients had similar strength on initial examination compared with untreated controls (mean SLSS 12.9 vs. 14.3, P = 0.313), but more severe paralysis at nadir (mean SLSS 9.25 vs. 12.82, P = 0.023) and latest follow-up (mean SLSS 12.5 vs. 16.4, P = 0.005) (Figure 2). In propensity-adjusted analysis, SLSS from initial examination to latest follow-up decreased by 0.2 (95% CI: −1.8 to +1.4) in fluoxetine-treated patients and increased by 2.5 (95% CI: +0.7 to +4.4) in controls ( P = 0.015). Conclusion: Fluoxetine was safely administered and relatively well-tolerated. Patients with AFM treated with fluoxetine were more likely to have EV-D68-associated disease and had more severe paralysis at nadir and poorer long-term outcomes. These data do not suggest a positive efficacy signal for fluoxetine as a potential antiviral therapy for AFM. Disclosures: All authors: No reported disclosures.